1968
DOI: 10.1103/physrev.171.1349
|View full text |Cite
|
Sign up to set email alerts
|

Wave Equations on a Hyperplane

Abstract: The Dirac equation, the Weaver-Hammer-Good wave equations, and the Weinberg wave equations are written in a manifestly covariant form in terms of hyperplane parameters according to Fleming's hyperplane formalism. A Fody-Wouthuysen-type wave equation is developed for the Weinberg theory and it, along with the usual Foldy-Wouthuysen wave equation and transformation, is also written in a manifestly covariant form for all spin. Fleming's formalism is extended to include the case where the hyperplane parameters are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

1970
1970
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…( 25) was firstly considered in [21] following a different approach, including electromagnetic interactions at the classical level. Closely related work was also done in [22], [23]. The present approach, based on the parity and Poincaré projections, permits us to identify all quantum numbers from first principles.…”
Section: B the Spin-one Parity Projectionmentioning
confidence: 98%

Spin one matter fields

Napsuciale,
Rodríguez,
Ferro-Hernández
et al. 2015
Preprint
“…( 25) was firstly considered in [21] following a different approach, including electromagnetic interactions at the classical level. Closely related work was also done in [22], [23]. The present approach, based on the parity and Poincaré projections, permits us to identify all quantum numbers from first principles.…”
Section: B the Spin-one Parity Projectionmentioning
confidence: 98%

Spin one matter fields

Napsuciale,
Rodríguez,
Ferro-Hernández
et al. 2015
Preprint
“…Similar arguments apply equally well to the arbitrary spin equations derived in Section 2 and to the arbitrary spin equation (2) of Joos and Weinberg considered in the Introduction. Hammer et al (1968) have shown that the hyperplane formalism of Fleming (1966) can be used to ensure that the wavefunction components of equation (2) always obey the Klein-Gordon equation. We considered an alternative procedure in Section 2.…”
Section: Pmentioning
confidence: 99%
“…In refs. [9,17,4,18,19] the Feynman diagram technique was discussed in the abovementioned six-component formalism for particles of spin j = 1. The following Lagrangian: 5,6…”
mentioning
confidence: 99%
“…The following expression has been obtained for the interaction vertex of the particle with a photon described by the vector potential, ref. [17,18]:…”
mentioning
confidence: 99%